THE MODIFIED SIMPLE EQUATION METHOD FOR NONLINEAR FRACTIONAL DIFFERENTIAL EQUATIONS - Kaplan, Melike; Bekir, Ahmet; Akbulut, Arzu; Aksoy, Esin (EDITURA ACAD ROMANE, 2015)
In this study, the modified simple equation method is used to construct exact solutions of the space-time fractional modified Korteweg-de Vries equation, the space-time fractional modified regularized long-wave equation and the space-time fractional coupled Burgers' equations in mathematical physics. The exact solutions obtained by the proposed method indicate that the approach is easy to implement and computationally very attractive. Also we can see that when the parameters are assigned special values, families of exact solitary wave solutions can be obtained by using this method.
Keywords: Exact solution; modified simple equation method; modified Riemann-Liouville derivative; space-time fractional differential equation; 1ST INTEGRAL METHOD; ZAKHAROV-KUZNETSOV; BURGERS EQUATIONS; WAVE SOLUTIONS; APPROXIMATION; SOLITONS; Physics